Views about Head Nurses' Directional Performance in Qom Educational Hospitals - Z Ghamari zare; GH Zand (Iran University of Medical Sciences, 2016)
Abstract Background & Aim: Effectiveness of Leadership activities and Skills in nurse managers have benefits for the health organizations. In this way directional performance plays an important role. The aim of the study was to investigate the head nurses' directional performance through self-measuring and nurse-measuring viewpoint in Qom educational hospitals in 2014. Materials & Methods: This was a descriptive study that all the head nurses (58) and nurses (202) in teaching hospitals of Qom in 2014 invited to study. Data was collected through a self-made questionnaire. This questionnaire was designed to determine the directional performance of head nurses. The analysis of internal reliability was done using the Cronbach alpha coefficient) 0.96(. Statistical analysis of data was carried out by descriptive and analytical statistics using SPSS ver. 21.0 software.  Results: Independent t-test showed a significant difference between the head nurses' directional performance through self-measuring and nurse-measuring viewpoint (P <0.05), so that head nurses had a more favorable view relative to their directional performance. Item of "appropriate reward system based on nursing practice" was the weakest performance from the perspective of nurses. Conclusion: There is a gap between the viewpoint of nurses and head nurses about the present status of directional performance in head nurses; then it is necessary that all the nurse managers try for self-empowerment and promote the quality of the directional performance process.